O lugar do gesto nas teorizações linguísticas - Cavalcanti, Daniel Rodrigues (2020)
The birth of a science is the moment of construction of categories and objects of analysis. This process of composing the elements is based on the climate of opinion (KOERNER, 1996) that builds the accepted and observable facts. Reading the peaceful points of a science is necessary to understand the possibilities of work that have been built over time from the categories and concepts accepted by the people who build scientific practice. This work has as main objective to observe how language studies and language approached - or did not do - the body as one of the parts of the discourse through the production of gestures. We will start from a historiographic view (VIEIRA, 2018; SWIGGERS, 2012) as a way to explain the use or not of gestures as a category of language analysis. After that, we will approach the hypothesis that the gesture is an integral part of the linguistic system (KENDON, 1972; KENDON, 1982; McNeill, 1985). In our analysis we used the concept of climate of opinion (AUROUX, 2014) and the concept of Traditional Paradigm for Gratification (PTG) (VIEIRA, 2018) as keys for our reading. Our investigative path uses historiographic criteria to select historical moments, authors and texts that can be analyzed. We started our approach in the constitution of classical Greek thought, advancing to the bases of linguistics (SAUSSURE, 2012), going through reflections of the philosophy of language and primatology (BAKHTIN, 2006; TOMASELLO, 2003) to reach the recent reflections on the use of gestures as part of a vocal gesture matrix (CAVALCANTE; BARROS, 2012; KENDON, 1982, 2000, 2009; MCNEILL, 2006; ÁVILA NÓBREGA, 2017; et al). The results we obtained are: the PTG works as a filter for linguistic work, not allowing the insertion of gestures as a category of analysis; the concept of language undergoes few changes in its deep epistemological root, remaining usually linked to writing and phonic material; works with multimodality and language acquisition are a space for a break with the PTG and can provide paths for a broad debate on the language.